Analisis Metanil Yellow Pada Minuman Sinom Di Surabaya Menggunakan Metode Spektrofotometri UV-Vis - Pramushinta , IAK; Fitriyati , Irenia Ida; Ambawarwati , Nadya (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Metanil yellow in food is very dangerous to human health. This is because this dye contains heavy metal residues that have been proven to cause cancer. Indonesian Minister of Health Regulation No. 239/Menkes/Per/V/85 prohibits the use of metanil yellow as a food dye, but this dye is often found in various markets. Objective: This study analyzed metanil yellow in sinom drinks circulating in the city of Surabaya. Methods: The analysis of metanil yellow dye included method validation using UV-Vis spectrophotometry on five samples of sinom drinks. Research Results: Theresults of the metanil yellow analysis in sinom drinks showed linearity with a regression of y = 0.0191x – 0.1774, an r2 value of 0.9961, an LOD of 1.30833 ppm, and an LOQ value of 4.36108 ppm. The precision value was RSD 1.19%. Accuracy values with average % recovery of 94.26% (80%), 94.66% (100%), and 92.91% (120%). In the analysis of metanil yellow from 5 samples circulating in the southern part of Surabaya, code C 0.001854%, west code A 0.002475%, center code C 0.001725%, east code B 0.001249%, and north code A 0.002823%. Conclusion: The UV-Vis spectrophotometry method has been validated and meets the requirements for preliminary screening analysis of metanil yellow. Preliminary screening results of five samples of sinom drinks circulating in the city of Surabaya showed indications of metanil yellow in all samples with concentrations ranging from 12.41 to 28.28 ppm. Due to the limited specificity of the UV-Vis spectrophotometry method, this study needs to be confirmed with more specific techniques such as HPLC or TLC to ensure the identity of the metanil yellow compound.